Pharmacological Assessment of Morinda CitrifoliaFruit Extract’s in Anti-Arthritic Properties in Wistar Rats - Yadav, Rajni; Malaiya, Saumya; Mishra, Shweta; Nisha, Parveen; Kumar Jain, Aarekh; Chaubey, Anshul; Khare, Basant (Journal of Neonatal Surgery, 2025)
Arthritis and related disorders, including rheumatoid arthritis (RA), are common diseases affecting millions of people. RA is characterized by articular injuries having an inflammatory propagation of synovial cells, attaining a nearly complete functional defect. It affects about 1% of the general population.Morinda citrifolia L(Rubiaceae), commonly called Noni or Indian mulberry, is a small evergreen tree or shrub of Polynesian origin. M. citrifolia bears a lumpy, green to yellowish-white fruit, normally 5 to 10 cm in length, with a surface covered in polygonal-shaped sections,The leaves, roots, bark and fruits have all been used medicinally to treat a wide range of ailments. These include, but are not limited to, diabetes, diarrhoea, hypertension, malaria, pain, and topical infections. The fruits are also eaten as a food, but primarily only in times of famine. The present study was designed to investigate anti-arthritic activity of methanolic fruits extract of M. citrifolia in Freund’s complete adjuvant (FCA)-induced arthritis in rats. Qualitative analysis of various phytochemical constituents was determined by the well-known test protocol available in the literature. The In vitro antioxidant activity of methanolic extract of the fruits was assessed against DPPH free radical scavenging assay method using standard protocols. M. citrifolia was evaluated for anti-arthritic action by Freund’s adjuvant induced arthritis test in adult Albino rats (200±20gm). Rats were injected 0.1 ml of complete Freund’s adjuvant into the planter region of the left hind paw. M. citrifolia extracts (200 and 400 mg/kg. b.wt.) was given orally to arthritic rats induced with Complete Freund’s Adjuvant and changes in rat paw volume and body weight was determined. Phytochemical analysis of methanolic extract of M. citrifolia showed the presence of carbohydrate, alkaloids, phenolics, tannin, triterpenoids, steroids, flavonoids and glycoside. In the oral acute toxicity studies, M. citrifolia was found to be safe as it did not cause any mortality up to 2000 mg/kg. Hence, 200 and 400 mg/kg doses were selected for the present study.DPPH radical scavenging activity of M. citrifolia extract exhibited percent inhibition 60.15% and its IC 50value was found to be 57.10μg/ml. Ascorbic was used as a reference compound which exhibited percent inhibition 86.36% and showed IC 50 value of 19.36μg/ml. M. citrifolia administered groups showed marked reduction in paw volume when compared with the negative control group (Group II). It was also found that there was significant weight loss when compared to standard. The results reveal promising anti-arthritic potential of the M. citrifolia. However further pharmacological investigation using isolated active ingredients can be carried out to confirm its efficacy and mechanism of action.